The Implementation of Human Resource Management in Improving the Quality of Teacher’s Learning - Subaidi Subaidi; Sudarmaji Sudarmaji; Moh Nasuka; Munasir Munasir (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
This article aims to describe the application of human resource management in improving the quality of teacher learning. The research used a qualitative approach, while the type of research was survey/field research. Collecting data using interview techniques, observation, and documentation. Furthermore, the collected data will be analyzed with data reduction techniques, data presentation, and finally drawing conclusions. The results of this research indicate that a) The application of human resource management in improving the quality of teacher learning: (1) Planning for Human Resource Needs (2) Procurement of Human Resources/Recruitment Staff. (3) Assessment of Work Performance and Compensation of Human Resources. (4) Human Resources Training and Development. (5) Creating and Fostering Effective Work Relationships. b) Supporting factors are support from student guardians, students, and school principals, leadership, human resources, facilities, culture. Inhibiting Factors are limited learning time, Less optimal education and teacher training development, Quality communication. c) The results of improving the quality of teacher learning through the application of human resource management are evidenced by the completeness and quality of teaching tools owned by teachers of SMK N 2 Jepara which include: RPP, journals, student attendance lists, question analysis, enrichment programs, and assessment instrument. So that each student has a Study Result Card, Value Transcript (report card), Portfolio, and Competency Certificate